Locating civic engagement through social media during calamities: The Philippine experience - Roldan, Maria Divina Gracia Z. (Animo Repository, 2015)
This paper explores how citizens use social media during calamities to express their opinions, generate resources, and mobilize support for disaster victims gleaning from the Philippine experience. It examines civic participation and the role of new media in disaster response and management specifically using Facebook and Twitter. The paper provides a glimpse on the prospects for online community building and civic engagement during disasters. It also seeks to provide insights to decision-makers on how to harness social networking sites to promote information dissemination, timely response, and participation from the citizenry on issues of public concern, particularly during natural disasters. © 2015 Common Ground, Maria Divina Gracia Z. Roldan, All Rights Reserved.